Perilaku Konsumen dalam Jual Beli Kredit Sepeda Motor Honda di Surabaya Menurut Perspektif Etika Bisnis Islam - Imelda Mega Sari (Nomicpedia: Journal of Economics and Business Innovation, 2022)
Humans are social beings who have goals and desires to fulfill all their needs, both primary, secondary and tertiary adequacy. One of the human needs to be obtained is to have a vehicle to meet daily needs. One of them is with the sale and purchase of motorcycle loans, it can make it easier for people to be able to meet their needs. The purpose of this research is to find out how consumers behave when doing a Honda motorcycle credit business in Surabaya from the point of view of Islamic business ethics. This research uses the type of field research method and the nature of the research is qualitative. The data sources used are primary data sources obtained directly from a seller and 12 Honda motorcycle users in Surabaya. Research data analysis technique is using qualitative analysis. In buying and selling Honda motorcycle loans in Surabaya, it is influenced by external (culture, social class and family) and internal (personal, and psychological) causes and has not fully implemented the principles of Islamic Business Ethics, due to consumer behavior that still violates or breaks promises what has been agreed in the sale and purchase.